Kajian Konsep Fisika Berbasis Kearifan Lokal Dalam Tari Bonet Suku Dawan - Bobu, Fetronela Rambu; Ludji, Dian Grace; Donuata, Pujianti Bejahida (UNIVERSITAS INDRAPRASTA PGRI, 2025)
The research conducted involves a study of the physics concepts that can be found in the movements of the Bonet dance. The focus of this research is to position the Bonet dance in different contexts according to the philosophy of the dance, relating it to the physics concepts within the dance movements. This study is qualitative in nature, using descriptive qualitative methods. The data sources consist of literature review and documentation. The results of the research show that physics concepts have been identified in the basic movements of the Bonet dance. Some of the physics concepts found in the movements of the Bonet dance include frictional force, equilibrium, momentum, inertia, and torque. This demonstrates that culture can be used to explain or illustrate physics concepts. Thus, the Bonet dance of the Dawan tribe can be used as a learning resource for students in physics classes.